Wildlife Management Failures, Successes and Prospects - Kideghesho, Jafari R.; Rija, Alfan A. (IntechOpen, 2019)
The decline of wildlife populations is increasingly posing a challenge to wildlife management agencies. In the face of increasing challenges such as wildlife diseases, human - wildlife conflicts, climate change, illegal hunting, and habitat loss, among others, new management models and strategies are being adopted to address these challenges. These models and strategies have, however, produced some mixed outcomes - both failures and successes. Wildlife Management - Failures, Successes and Prospects provides an understanding of some of the realities shaping wildlife management policies in different parts of the world. Drawing from case studies, the book presents some challenges facing wildlife management and the emerging management models, strategies, options for action, and success stories. This book offers a real field experience to conservation practitioners, planners, researchers, academicians, and students.